PERANCANGAN MODEL M-LEARNING BERBASIS MULTIMEDIA MENGGUNAKAN SELULAR CDMA - Santoso, Gatot (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
Collaboration of cellular CDMA with mobile learning (M-Learning) is the best choise. Because m_learning needed a big capacity (large video) in managing of multimedia matery. Designing did build a server and client system with combination of HTML script as web server apllications and web client and WML script as WAP site aplication. Afficasious from this research is the power control thecnical that has not maximal in the spread of power to mobile station at the some periode.